Gate voltage enhances the thermoelectric transport of quantum dots in graphene nanoribbons - Amorim, Felippe P. [UNESP]; Torres, Alberto [UNESP]; Villegas, Cesar E.P.; Rocha, Alexandre R. [UNESP] (My University, 2023)
Chemically derived graphene nanoribbons and quantum dots are unique nanostructures that offer more possibilities than 2D and 3D systems to tune their electronic properties due to the enhanced quantum confinement effects. This feature make them potential candidates for many technological applications, including thermoelectrics. In this work, we combined density functional theory calculations with the non-equilibrium Green's function formalism to investigate the electronic and thermoelectric properties of recently synthesized quantum dots in graphene nanoribbons under the presence of an applied gate voltage, and for different temperatures. We find that the electronic states at the band edge are highly localized in the inner region of the quantum dot, and can be lifted to higher energies by applying a gate voltage, which subsequently enhances figure of merit. Moreover, at zero gate voltage and room temperature, we estimate the lower bound for ZT to be approximately 0.25. Interestingly, this lower bound can exceed unity by smoothly increasing the gate voltage for values above 6 V. The overall results regarding the enhancement of ZT suggest that quantum dots in graphene nanoribbons would be promising candidates for thermoelectric applications.
Keywords: 7-14-7 AGNR; Gate voltage enhances; Quantum dots in graphene; Thermoelectric transport